PESAN LAYANAN MRT (MODA RAYA TERPADU) TERHADAP KEPATUHAN PENUMPANG - SITI KHADIJAH; NADHIAHTUL ATHIYAH (Interpretasi: Communication & Public Relations, 2022)
The presence of public service transportation MRT (Mode Raya Terpadu) is expected to be a solution to meet the mobility needs of the Jabodetabek population en masse and quickly. To ensure the comfort and safety of passengers, MRT applies various rules that are socialized to all passengers in the form of verbal and non-verbal messages. This study aims to examine the significance of the effect of MRT service messages on passenger compliance. This study uses an explanatory descriptive method, with a quantitative approach. The sampling technique used was accidental sampling with a sample size of 100 passengers. Data collection techniques using questionnaires and interviews. The analysis technique uses linear regression. The results in this study state that the MRT service message has an effect of 16.8% on passenger compliance, then the remaining 83.2% are other factors such as the advantages of the MRT, sanctions, and the impact of the presence of the MRT. MRT service messages have a positive and significant effect on MRT passenger compliance with a coefficient value of 0.885.